ROLLI O'YINLAR VOSITASIDAN ZAMONAVIY O'QITISHDA SAMARALI FOYDALANISH METODIKASI - Yusupova Nargiza Nigmatovna (FAN, TA'LIM VA AMALIYOT INTEGRATSIYASI, 2020)
This article, devoted to role-playing games in modern teaching methods, has a great influence on the development of students ' speech abilities. It is compensated by recreating real speech situations through role-playing games in order to increase the communicative component of the language being studied. In this article, the concept of "role-playing games" is understood as created situational and variable exercises of a natural nature. The article describes the typology of role-playing games, developed materials and their delivery to students